Examination on the physical properties of untreated kenaf insulation paper at different beating degrees - Muhammad Umair; Norhafiz Azis; Rasmina Halis; Jasronita Jasni (Institute of Advanced Engineering and Science, 2020)
This paper examines the physico-mechanical properties of untreated kenaf based insulation paper with consideration on different beating degrees. Kenaf bast fibers were first processed through soda pulping process. Different beating degrees were subjected to the processed pulps. Physical parameters of the paper were measured for each of the beating degrees. It is found that as the beating revolution increases, the kenaf based insulation paper’s density, tensile index and burst index increase while thickness and tear index decrease.